ATOMi An Algorithm for Circuit Partitioning Into Multiple FPGAs Using Time-Multiplexed, Off-Chip, Multicasting Interconnection Architecture. - Kwon, Y.-S (IEEE Transactions on VLSI systems)
Logic emulation is so far the fastest method to verify the system functionality in the gate level before chip fabrication. Field-programmable gate array (FPGA)-based logic emulator with large gate capacity generally comprises a large number of FPGAs or special processors connected in mesh or crossbar topology. However, gate utilization of FPGAs and speed of emulation are limited by the number of signal pins among FPGAs and the interconnection architecture of the logic emulator. This paper first describes a new interconnection architecture called TOMi (Time-multiplexed, Off-chip, Multicasting interconnection) and proposes a circuit partitioning algorithm called ATOMi (Algorithm for TOMi) for multi-FPGA system incorporating four to eight FPGAs where FPGAs are interconnected through TOMi. ATOMi reduces the number of off-chip signal transfers to optimize the performance for multi-FPGA system implemented by TOMi. Experimental results using Partitioning93 benchmarks show that, by adopting the proposed TOMi interconnection architecture along with ATOMi, the pin count is reduced to 14.4%?88.6% while the critical path delay is reduced to 66.1%?90.1% compared to traditional architectures including mesh, crossbar, and VirtualWire architecture.